2021
DOI: 10.1021/acsami.1c12142
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of Graphene through Heterobifunctional Supramolecular-Covalent Scaffolds for Rapid COVID-19 Biomarker Detection

Abstract: Graphene is a two-dimensional semiconducting material whose application for diagnostics has been a real game-changer in terms of sensitivity and response time, variables of paramount importance to stop the COVID-19 spreading. Nevertheless, strategies for the modification of docking recognition and antifouling elements to obtain covalent-like stability without the disruption of the graphene band structure are still needed. In this work, we conducted surface engineering of graphene through heterofunctional supra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…For the robust immobilization of affinity-proteins and antifouling polymers, surface engineering of GFETs through heterobifunctional supramolecular-covalent scaffolds based on VS-PEI (Figure 1F) was conducted as previously described. [33] Briefly, VS-PEI scaffolds were constructed onto GFETs by three simple surface modification steps: 1) the adsorption of pyrenebutanoic acid succinimidyl ester (PBSE) on graphene; 2) the fast reaction of polyethyleneimine (PEI) in aqueous solutions with surface-bound PBSE; and 3) the modification of remaining primary amine groups with divinylsulfone (DVS, a well-known cross-linker of SH, NH 2 , and OH groups via Michael type addition), [48][49][50][51] yielding VS-PEI on graphene. In these scaffolds, one side binds graphene through multivalent π-π interactions with pyrene groups, and the other side presents vinylsulfonated pending groups that can be used for covalent binding.…”
Section: Electrical Characterization and Functionalization Of The Gfetsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the robust immobilization of affinity-proteins and antifouling polymers, surface engineering of GFETs through heterobifunctional supramolecular-covalent scaffolds based on VS-PEI (Figure 1F) was conducted as previously described. [33] Briefly, VS-PEI scaffolds were constructed onto GFETs by three simple surface modification steps: 1) the adsorption of pyrenebutanoic acid succinimidyl ester (PBSE) on graphene; 2) the fast reaction of polyethyleneimine (PEI) in aqueous solutions with surface-bound PBSE; and 3) the modification of remaining primary amine groups with divinylsulfone (DVS, a well-known cross-linker of SH, NH 2 , and OH groups via Michael type addition), [48][49][50][51] yielding VS-PEI on graphene. In these scaffolds, one side binds graphene through multivalent π-π interactions with pyrene groups, and the other side presents vinylsulfonated pending groups that can be used for covalent binding.…”
Section: Electrical Characterization and Functionalization Of The Gfetsmentioning
confidence: 99%
“…From these results it can be concluded that our functionalization approach does not disrupt the semiconducting properties of graphene, as previously demonstrated. [33] Next, recognition elements were bound to VS-PEI scaffolds prepared onto the graphene transistor. Three affinity-proteins were used as recognition elements: 1) Concanavalin A (ConA), a well-known lectin with high affinity to glycans; 2 a mAb specific to SARS-CoV-2 spike protein; 3) a mAb specific to human ferritin.…”
Section: Electrical Characterization and Functionalization Of The Gfetsmentioning
confidence: 99%
See 2 more Smart Citations
“…These scaffolds offer vinylsulfonated awaiting groups for covalent attachment on one side and multivalent pyrene groups on the other. Construction of PA-VS scaffolds was shown using contact angle measurements and Raman spectroscopy [108]. Soft and hard tissue repair and regeneration, as well as wound healing, are possible using electrospun nanofiber scaffolds.…”
Section: Regeneration Of Lung Tissue Using Biopolymeric Scaffoldsmentioning
confidence: 99%